Conceptualizing Social Enterprise in the lense of Islamic Perspective / Saunah Zainon ... [et al.] - Zainon, Saunah; Yoke, Soo Kum; Mohamed Yunos, Rahimah; Md Yatim, Nurul Huda; Mokhtar, Rashidah; Japelus, Nur Eyliawati (2021)
In general, social enterprises have two uncompromising roles which are first, to generate economic impact and secondly, to infuse a social impact. This is especially essential with the rise in poverty and other major social problems. The seriousness of the problem can be seen in the government's efforts towards reducing the level of poverty and social problems by inducing RM50 million boost. In SDG 1 (Sustainable Development Goal), additionally, poverty eradication and social restructuring have been prioritised. Islamic social enterprises have also become more pronounced in recent times with their focus on zakat (obligatory charity), sadaqa (voluntary charity), and waqf (perpetual endowment).According to Austin et al. (2006), Certo and Miller (2008), and Zahra et al. (2019), social entrepreneurship are NGOs (Non-governmental Organizations) or NPOs (Non-profit Organizations) that operate to fulfill the unmet social needs as well as to create social values in society through entrepreneurial processes. Emerson et al. (2020) further state that it addresses social challenges and problems from poverty to health, education to the environment. A major problem that has been of utmost unrest, however, is the way finances in social enterprises (SEs) are handled. Mismanagement and mishandling of funds have led to fraud cases and untold criminal activities. This inevitably has led to public mistrust.